2014
DOI: 10.1080/03079457.2014.939942
|View full text |Cite
|
Sign up to set email alerts
|

Progress and problems in vaccination against necrotic enteritis in broiler chickens

Abstract: Necrotic enteritis in broilers is caused by Clostridium perfringens type A strains that produce the NetB toxin. Necrotic enteritis is one of the gastrointestinal diseases in poultry that has gained worldwide importance during the last decade due to efforts to improve broiler performance. Prevention strategies include avoiding predisposing factors, such as coccidiosis, and in-feed supplementation with a variety of feed additives. However, vaccination with modified toxin or other secreted immunogenic proteins se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 79 publications
3
35
0
Order By: Relevance
“…The designation of fusion subunit vaccine encompassing the immunogenic segments from individual toxin against NE is a promising recent approach [8]. Mot et al and Uzal et al, have shown for protection against NE, administration of multiple antigens like Alpha-toxin and NetB toxin could elicit better immunogenicity and protection than each antigen alone [16,32]. Rostami et al, designed a fusion protein consisting of immunogenic parts of three virulence factors of NetB-Alpha toxin-Tpel(NAT) to be used as vaccine against necrotic enteritis [27].…”
Section: Discussionmentioning
confidence: 99%
“…The designation of fusion subunit vaccine encompassing the immunogenic segments from individual toxin against NE is a promising recent approach [8]. Mot et al and Uzal et al, have shown for protection against NE, administration of multiple antigens like Alpha-toxin and NetB toxin could elicit better immunogenicity and protection than each antigen alone [16,32]. Rostami et al, designed a fusion protein consisting of immunogenic parts of three virulence factors of NetB-Alpha toxin-Tpel(NAT) to be used as vaccine against necrotic enteritis [27].…”
Section: Discussionmentioning
confidence: 99%
“…Although NetB has been identified as a key toxin involved in disease (Keyburn et al, 2008), this has still not led to the development of a vaccine for broilers (Mot et al, 2014). Several antigens in addition to NetB seem to be important in immunoprotection.…”
Section: Editorialmentioning
confidence: 99%
“…Originally, alpha toxin was considered to be the main virulence factor for NE, until the NetB toxin was identified as a crucial factor in disease pathogenesis (Keyburn et al, 2008;. Since then, a lot of research has been conducted on the identification of risk factors, pathogenesis, and preventive measures of NetB-associated NE (Mot et al, 2014;Moore, 2016;Prescott et al, 2016;Wade et al, 2016Wade et al, , 2020Calik et al, 2019). However, despite the overwhelming evidence of the importance of NetB-producing type G strains in NE pathogenesis, this is still a matter of debate in the scientific community, with some research groups describing the isolation of netB-negative type A strains from diseased birds (Yin et al, 2017;Li et al, 2018;Zhang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%